Research on Key Evaluation Technology for Face Recognition Based on Public Security Traffic Management Business (Innovative Applications of AI, 2024)
With the continuous improvement of face recognition technology, it has been widely applied in various important scenarios, including public security traffic management. Although preliminary results have been achieved in face recognition technology, there is still a lack of authoritative testing and evaluation for the quality of face recognition algorithms. The testing standards for face recognition systems used in face model training and algorithm testing are generally associated with specific application scenarios. Due to the lack of a systematic and standardized general performance testing specification for face recognition systems oriented towards the field of public security traffic management, this paper mainly analyzes the face recognition scenarios in public security traffic management. It aims to study the key evaluation technology methods and indicators in conjunction with different business application scenarios, according to the relevant industry standards of face recognition, and to build a test library for various face recognition scenarios. This will further improve the application effectiveness of face recognition systems in the field of public security traffic management.